UMP and Pahang State Government collaborate in big data analytics - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
KUANTAN, 5 October 2022 - Universiti Malaysia Pahang (UMP) is working with the Pahang State Government on big data analytics to develop training programmes involving State Government officials. This collaboration also involves research through the information sharing of the Pahang State Secretariat Office with the lecturers of the Faculty of Computing at the university.